The effect of fasting time of white snapper (Lates calcarifer) seeds transported for seven hours on survival rate - Mislina, Mislina; Rahmayanti, Fitria; Hendri, Afrizal; Diansyah, Sufal; Islama, Dini; Munandar, Munandar (Acta Aquatica: Aquatic Sciences Journal, 2025)
The availability of white snapper seeds is still as a problem which is there are still limited in some places and only seals in certain areas in Indonesia. So proper seed handling techniques are needed to increase their survival. This research aims to obtain the optimal fasting duration for white snapper seeds before transportation. Transportation was conducted in closed system, transported using a car, for 7 hours. This research was conducted at Ujung Batee Brackish Water Aquaculture Fisheries Center (BPBAP). The research used a Completely Randomized Design with four treatments and three replications, namely: transportation of white snapper seeds with fasting period of 12 hours (A), 24 hours (B), 36 hours (C) and 48 hours (D). The data obtained was tested for statistical analysis of variance (ANOVA) using SPSS 25.0. The results showed that different fasting duration had no significant effect (P>0.05) on the survival rate either after transportation or five days post-transportation.Keywords: fasting; seed; survival rate; transportation